Algorithm of Development for Stabilization of Socio-Ecological Situation in Karakalpakstan - Alisher Abdullaev (Qubahan Academic Journal)
The relevance of developing a scientific framework for stabilizing the socio-ecological situation of the Republic of Karakalpakstan is determined by the need to address the environmental, social and economic challenges faced by the region. It is designed to improve the population’s quality of life, sustainable development and balanced interaction with the environment. The purpose of the research was to establish the relationship between social and environmental factors, to establish a mathematical model based on them, which will enable predicting future development and establishing a set of recommendations to improve the situation in the Republic of Karakalpakstan. The methods of theoretical analysis and mathematical modelling were used. The research outlines modern ideas about modelling the dynamics of socio-ecological processes in the example of the Republic of Karakalpakstan. It is established that the Republic has several problems, the solution of which should be started shortly. Considerable attention is paid to the setting of tasks and using for this purpose methods of system analysis of socio-ecological factors. In this work, the analysis of factors affecting the social and environmental environment of the Republic of Karakalpakstan using regression analysis is considered. The parameters of the developed mathematical model and their adequacy are determined. The developed mathematical model will allow identification of the social and ecological situation of the republic. At the end of the work, ten priority points for the next 5-10 years to improve the socio-ecological situation were presented. The practical value of the results is implemented in promoting the identification of new powerful reserves for further improvement of the management of social processes. This approach allows for increasing the national economic efficiency of the region and ensuring a balance between economic, social and environmental aspects of development, which is an essential step towards a sustainable future.